Aging, Obesity, and Motor Vehicle Collisions - Lavallière, Martin; Tremblay, Mathieu; Lefebvre, Frédéric; Billot, Maxime; Handrigan, Grant A. (Frontiers in Sustainable Cities, 2020)
Aging and obesity are two key areas of research as risk factors leading to motor vehicle collisions (MVCs). However, only a few studies identified obese older drivers as an at-risk population of MVC (i.e., older than 65 years old with Body Mass Index greater than 30 kg/m2). This paper aims to review the literature related to aging, obesity, and MVCs. Extensive literature searches were conducted, and the results are presented in a narrative review of the literature, in order to discuss the risk for involvement in MVC as well as the solutions for this population. Extrinsic factors are components of the “built environment” that decrease road safety for this population and poor fit of the vehicle through their inappropriate design for this population. The intrinsic factors are the autonomy and the health status of the driver. Health status are challenges associated with obesity and aging that increase the prevalence of being part in a MVC and that increase risk of morbidity and mortality during or following a collision. Finally, some prevention strategies are presented for consideration. There is a need to inform public policy makers on the additional risk factors associated with aging and obesity for MVCs.